Literacy for what? Contradictions in Swazi Adult Education - David Jele (Adult Education Research Conference, 2004)
The purpose of this paper is to examine the role of literacy in development in Swaziland. It seeks to identify in the process, contradictions that manifest in Swazi education generally and adult education specifically. It then highlights whose interests a given literacy level – high or low - serves and why.